The Relationship Between Incentives Satisfaction With Job Satisfaction,Loyalty,Job Career Life,Performance Appraisal And Ethic Of Incumbents Among Employees In The Ministry Of Education At Sultanate Of Oman - Fathiya Khalfan Sulaiman (Universiti Sains Islam Malaysia, 2024)
The study investigates incentives role and impacts as a key factor in addressing the issues of the employees' productivity improvement in the working environment in the Ministry of Education in the Sultanate of Oman. It is an attempt to examine the theme of the study with a view to prescribe a set of new proposal of incentives for the employees in the Ministry to ensure high productivity and job stratification. The study answers a set of questions in the given scenario, enquires into its philosophical and theoretical framework and examines its hypotheses with statistical evidences and recommends corrective measures. Also, the study employs descriptive analytical method. The sample space of this enquiry is confined to the employees in the cadre of supervisors and administrators of the Ministry of Education for the year 2015/2016. The population is drawn from Muscat, North Al Batinah, South Al Batinah and Al Dhahira regions and 69.5 % are males and 31.5% are females. The data is analyzed using the statistical package for social sciences. The analysis deployed in the discussion tries to relate the data and its findings to the hypothesis of the thesis. Apart from the normal statistical methods, Tukey Multiple Comparison, and one way Anova Test are also used in the thesis wherever necessary. The first part of the study deals with the degree of stratification of the employees over different indicators through financial incentive, moral incentives, training incentives and job caring incentives. The study portrays that degree of the satisfaction over these indicators are law. The second part of the study deals with the importance of these indicators in the job environment matrix based on the data which suggest high numerical value. Similarly, the justifications and impact factors are also found to be of high significance. Obviously, the reality brought out in the first part and the desirability discerned in the second part requires the study to address the gap through a set of new proposal of incentives to ensure better performance. It constitutes the recommendations of the study which are discussed in the third part. Therefore, the study addresses issues of high importance in the human resources enhancement strategies to be deployed in the ministry.